SPA-TYPING OF STAPHYLOCOCCUS AUREUS ISOLATED IN ASTANA - Kairzhanova , A.D.; Temirbayeva , M.A.; Atygayeva , S.K.; Abdrakhmanova , Zh.U.; Shvedyuk , V.B.; Shustov , A.V.; Stoyanova , L.G.; Kuibagarov , M.A.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2018)
Staphylococcus aureus colonization presents as a wide range of clinical infections and can lead to severe complications including death in human subjects. Currently, routine monitoring practices include methods of genetic fingerprinting for tracing outbreaks, as well as for global epidemiological studies. The use of rapid PCR-based methods including SPA-typing allow for classification of isolates with high virulence and drug resistance. The purpose of this study was to characterise isolates from Astana city hospital inpatients in 2017. A total of 153 isolates were collected. SPA-type could not be identified for seven samples, whereas as many as 61 SPA-types were found for the remaining 146 isolates. The most prevalent SPA-types were: t521 (10.6%), t267 (9.8%), t002 (6.5%), t024 (5.9%) and t091 (5.9%). Notably, low antibiotic resistance was found in 3.2% of MRSA isolates and in 7.8% of MSSA-MDR isolates. In 153 strains of S. aureus, a high percentage of resistance was found to trimethoprim (96.7%) and penicillin (84.3%). Erythromycin, clindamycin and tetracycline resistance were recorded in 6.5% of the isolates, and chloramphenicol, oxacillin, cefoxitin, doxycycline, ciprofloxacin and gentamicin resistance did not exceed 4%. All isolates were sensitive to vancomycin, linezolid and rifampicin. Regular monitoring can improve treatment program effectiveness and help to control the circulation of antibiotic resistant strains.